Simulation-Based Learning Enhances Sport Massage Competence in Physical Education Students: A Quasi-Experimental Study - Alwi Fahruzy Nasution; Retha Foret (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This study aimed to examine the effectiveness of simulation-based learning (SBL) in improving sport massage competencies among Physical Education students, with particular emphasis on psychomotor skill development and applied performance outcomes. Materials and methods. A quasi-experimental one-group pretest–posttest design was employed. Thirty undergraduate Physical Education students (18 males, 12 females) enrolled in a Sport Massage course participated in the study. The intervention consisted of four simulation-based learning sessions designed to replicate authentic sport massage scenarios. Sport massage competence was assessed using a validated observation rubric covering massage technique, procedure sequence, pressure and rhythm control, and therapeutic communication. Data were analyzed using descriptive statistics, paired-sample t-tests, Cohen’s d effect size, and normalized gain (N-Gain) analysis at a significance level of α = .05. Results. The results demonstrated a statistically significant improvement in overall sport massage competence following the SBL intervention (t(29) = −12.46, p < .001). The mean score increased from 68.40 (SD = 6.32) at pretest to 84.27 (SD = 5.41) at posttest, yielding a large effect size (Cohen’s d = 2.28). Component-level analysis revealed significant gains across all assessed skills (p < .001), with the largest improvements observed in pressure and rhythm control and massage technique. The overall N-Gain score was 0.70, indicating high learning effectiveness, with 96.67% of participants achieving moderate-to-high learning gains. Conclusions. Simulation-based learning is a highly effective instructional approach for enhancing sport massage competencies among Physical Education students. By providing realistic, structured, and repetitive practice opportunities, SBL facilitates meaningful psychomotor skill acquisition, improves performance consistency, and supports professional readiness. The integration of simulation-based strategies is strongly recommended for sport massage instruction in higher education physical education programs.